2021
DOI: 10.1590/jatm.v13.1233
|View full text |Cite
|
Sign up to set email alerts
|

A Literature Survey of Unmanned Aerial Vehicle Usage for Civil Applications

Abstract: Unmanned vehicles/systems (UVs/USs) technology has exploded in recent years. Unmanned vehicles are operated in the air, on the ground, or on/in the water. Unmanned vehicles play a more significant role in many civil application domains, such as remote sensing, surveillance, precision agriculture and rescue operations rather than manned systems. Unmanned vehicles outperform manned systems in terms of mission safety and operational costs. Unmanned aerial vehicles (UAVs) are widely utilized in the civil infrastru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(23 citation statements)
references
References 69 publications
0
22
0
1
Order By: Relevance
“…This is due to the fact that they are widely used in traditional areas such as logistics, monitoring of the environment and industrial facilities, search and rescue operations, etc. [28]. In addition, recently, UAVs have been being used in completely new areas: monitoring crop diseases, landslides, mountain ranges, etc.…”
Section: Discussionmentioning
confidence: 99%
“…This is due to the fact that they are widely used in traditional areas such as logistics, monitoring of the environment and industrial facilities, search and rescue operations, etc. [28]. In addition, recently, UAVs have been being used in completely new areas: monitoring crop diseases, landslides, mountain ranges, etc.…”
Section: Discussionmentioning
confidence: 99%
“…They found that the UAV‐based inspection performed well on building safety inspection and intended UAVs to be applied more in the future even though there were still several technical issues to be solved. Sivakumar and Malleswari 12 conducted a comprehensive overview and a literature survey of UAV usage for civil applications, including main components, classification, and categorization of UAV devices based on size, range, properties, and applications. Based on this summary, they pointed out that UAVs can capture a large amount of outstanding high‐quality photography data due to their excellent cameras equipped with top‐notch sensors, which are highly favored by a considerable number of application fields.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Currently, UAVs are used in various areas of human activity, logistics, monitoring of the environment and industrial facilities, search and rescue operations, agriculture, remote sensing of the Earth, etc. (Arkin 2015;Kostin and Bogatov 2019;Scharre 2018;Sivakumar and Malleswari 2021;Sloggett 2014). Some of the main trends in the development of unmanned aerial technologies are:…”
Section: Introductionmentioning
confidence: 99%